Rates of oxygen uptake increase independently of changes in heart rate in late stages of development and at hatching in the green iguana, Iguana iguana - Sartori, Marina R. [UNESP]; Abe, Augusto S. [UNESP]; Crossley, Dane A.; Taylor, Edwin W. [UNESP] (Elsevier B.V., 2017)
Oxygen consumption (VO2), heart rate (f(H)), heart mass (M-h) and body mass (M-b) were measured during embryonic incubation and in hatchlings of green iguana (Iguana iguana). Meanf(H) and VO2 were unvarying in early stage embryos. VO2 increased exponentially during the later stages of embryonic development, doubling by the end of incubation, whilef(H) was constant, resulting in a 2.7-fold increase in oxygen pulse. Compared to late stage embryos, the mean inactive level of VO2 in hatchlings was 1.7 fold higher, while fH was reduced by half resulting in a further 3.6 fold increase in oxygen pulse. There was an overall negative correlation between meanf(H) and VO2 when data from hatchlings was included. Thus, predicting metabolic rate as VO2 from measurements of f(H) is not possible in embryonic reptiles. Convective transport of oxygen to supply metabolism during embryonic incubation was more reliably indicated as an index of cardiac output (COi) derived from the product of f(H) and Mb. However, a thorough analysis of factors determining rates of oxygen supply during development and eclosion in reptiles will require cannulation of blood vessels that proved impossible in the present study, to determine oxygen carrying capacity by the blood and arteriovenous oxygen content difference (A-V cliff), plus patterns of blood flow. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Iguana; Reptile; Embryo; Growth; Oxygen uptake; Heart rate; Oxygen pulse